2012
DOI: 10.5805/ksci.2012.14.6.918
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Characteristics of Face in the Late Joseon-dynasty's Beauty Paintings

Abstract: : This study identified the aesthetic characteristics of the face description in late Joseon Dynasty beauty paintings. A total of 24 beauty paintings were selected as representative of the late Joseon Dynasty genre of painting works. The paintings were analyzed by the shape, color, and physiognomy of beauty trends from the components of women's faces expressed in the works of artists. The results of this study showed that the shape of the face components expressed a round, curved and thin line. Colors were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Women whose lives are dependent on men were called 'flower willows.' In various paintings depicting beautiful women, weeping willows are often present in the background (Lee et al, 2012). This may be because the waists of beautiful women were often compared to thin willow branches and also because the weeping willow and slender women fit nicely into a picture together.…”
Section: Add To That a Sweet Smilementioning
confidence: 99%
“…Women whose lives are dependent on men were called 'flower willows.' In various paintings depicting beautiful women, weeping willows are often present in the background (Lee et al, 2012). This may be because the waists of beautiful women were often compared to thin willow branches and also because the weeping willow and slender women fit nicely into a picture together.…”
Section: Add To That a Sweet Smilementioning
confidence: 99%
“…Relatively few paintings of young women were created in the Joseon dynasty. In an analysis of 24 paintings of Joseon beauties, Lee and Ku wrote that beauties had the following facial compositions: a round-forehead, thin crescent-shaped eyebrows (a sign of wisdom and sensitivity), single long thin eyelids (longevity), a round curved nose (as a symbol of being a wise mother or good wife), small concave lips (a sign of gentleness and intelligence), and a round face (as an indicator of insight and good memory) 2 …”
mentioning
confidence: 99%
“…In an analysis of 24 paintings of Joseon beauties, Lee and Ku wrote that beauties had the following facial compositions: a roundforehead, thin crescent-shaped eyebrows (a sign of wisdom and sensitivity), single long thin eyelids (longevity), a round curved nose (as a symbol of being a wise mother or good wife), small concave lips (a sign of gentleness and intelligence), and a round face (as an indicator of insight and good memory). 2 Comparing the shape of eyebrows in the Joseon dynasty to those in present Korea, different preferences are noted. Although the preferred eyebrow shape of the Joseon dynasty was thin and rounded, the preference of present Koreans is for eyebrows to be relatively thick with a specific shape: a prior study found that the "Anastasia type" (brow starts on a perpendicular line drawn from the middle of the nostril, arches on a line drawn from the center of the nose through the center of the pupil, and ends on a line drawn from the edge of the corresponding nasal ala through the outer edge of the eye) was the most preferred.…”
mentioning
confidence: 99%